Hatter M. Vol. 4, Zen of wonder - Beddor, Frank; Cavalier, Liz (Hatter M, 2013)
Royal Bodyguard Hatter Madigan's search takes an unexpected detour in the Zen of Wonder when he travels 'within' guided by a mischievous and often maddening young girl named Nekko. Nekko's origin is a Zen mystery, but her devotion to Hatter's quest to find the lost Princess is unwavering. After Nekko leads him on a fearless chase across the rooftops of 1871 San Francisco, Hatter must acknowledge her as a teacher!